(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The gap between the grand vision of developing the New Capital City (IKN) as a modern and sustainable city and realizing investment is still limited, so further studies are needed on the challenges and practical investment strategies. This study aims to examine the urgency and obstacles to investment in supporting sustainable and inclusive city development. This research relies on online research methods by relying on data sources from the official website of the Indonesian government. The data obtained were then analyzed using the Nvivo 12 Plus analysis tool with a thematic analysis approach. This study shows that the urgency of developing the New Capital City (IKN) is driven by the complexity of problems in Jakarta and the need for equitable development and climate resilience. Although investment interest is relatively high, with 304 letters of interest in 2023, investment realization until 2025 is still limited, indicating a gap between intention and implementation. The main challenges include the sustainability of environmentally friendly investment, energy efficiency, social inclusion, and financial sustainability. Therefore, concrete strategies are needed, such as simplifying regulations and fiscal incentives, strengthening public-private partnerships, developing transparent, integrated digital platforms, and providing state guarantees to strengthen investor confidence and accelerate the realization of IKN as a sustainable and inclusive city.